حق الزوجة في الخلع وحكم القاضي بين الكشف والإنشاء - شوكة فضيلة; جيرب شهيناز; د/ورنيقي محمد (جامعة عمار ثليجي الاغواط, 2023)
الحمد لله رب العالمين والصلاة والسلام على أشرف المرسلين سيدنا وحبيبنا محمد صلى الله عليه وسلم ومن تبعه بإحسان إلى يوم الدين، أما بعد : جعل الله تعالى الطلاق في عصمة الرجل وحق له وفي مقابل هذا كان للزوجة الحق في أن تخالع نفسها مقابل تعويض مالي تدفعه ل زوجها وهذا لدفع الضرر إذا كانت تبغض زوجها ولا تطيق العيش بجواره. وقد أعطى المشرع الج ا زئري للزوجة الحق في مخالعة نفسها من زوجها دون موافقته وهذا بعد تعديله للمادة 54 من قانون الأسرة، وحكم القاضي في الخلع منشئ وليس كاشف، وهذا له تأثير في مسألة العدة والمي ا رث وثبوت النسب للأولاد فالآثار الناجمة عن الخلع لا تري ألا من تاريخ حكم القاضي به . الكلمات المفتاحية: الخلع – الكشف – الإنشا ء Summary: Praise be to Allah, the lord of the worlds, and prayers and peace be upon the most honorable of messengers, our master and beloved Muhammad, may God’s prayers and peace be upon him, and those who followed him in goodness until the Day of Judgment. To proceed: God Almighty made divorce in the man's infallibility and his right, and in exchange for this, the wife had the right to divorce herself in return for a financial compensation that she paid to her husband, and this is to ward off the harm if she hates her husband and cannot bear to live next to him. The Algerian legislator gave the wife the right to divorce herself from her husband without his consent, and this is after amending Article 54 of the Family Law, and the judge’s ruling on divorce is established and not revealed, and this has an impact on the issue of the waiting period, inheritance, and establishing lineage for the children. The effects resulting from the divorce can only be seen from the date of the judgment judge it